Measuring the Effect of Foreign Aidon Growth and Poverty Reduction or the Pitfalls of Interaction Variables - Polak, J. (IMF Working Papers; Working Paper ;, 2007)
Regressions in a number of recent papers written by staff members of the World Bank and the IMF rely on an interaction variable (IAV) to establish the effects of foreign aid on economic growth or the reduction of poverty. The common assumption in these papers is that if the coefficient of this IAV is statistically significant, then both of its components have a significant effect on the dependent variable. That assumption is not justified in its generality, and this paper develops two techniques that show a high probability that in at least two of the three studies analyzed one of the components of the IAV may not have a significant effect.